La narración, una experiencia que potencia saberes: aportes a las directrices del decreto 2247 de septiembre 11 de 1997 (2020)
During the configuration of life as a student and becoming the dream of being a teacher, it is essential to approach and carry out transformations based on different theories and with the actions of the same being which produces a constant change towards the varied education. In pedagogical work, difference is a means of building not only knowledge and concepts, but a coexistence and constant action to think about the place of the other and the importance of it. The narrative is approached as a mediator to tell stories from personal experiences or anecdotes, where participation and leadership are part of the different actors who live and coexist around a teacher, as well as the desire to speak, imagine, remember and of course express themselves as part of an experience and exchange of knowledge that contribute new concepts to these cultures and the configuration of knowledge in common.